2010
DOI: 10.1039/b915566j
|View full text |Cite
|
Sign up to set email alerts
|

Tautomerism of the natural thymidine nucleoside and the antiviral analogue D4T. Structure and influence of an aqueous environment using MP2 and DFT methods

Abstract: A comparative theoretical conformational analysis of the tautomerism of the four most stable conformers of the antiviral analogue D4T (stavudine) and natural thymidine (Thy) nucleosides was carried out, by using the B3LYP and MP2 quantum chemical methods. The calculated structure data and energy values of the tautomers were compared with the T1 keto form and with the results determined for the thymine molecule. For each conformer, only two stable enol forms, T3 and T5, were obtained when considering different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 114 publications
3
19
1
Order By: Relevance
“…From a rigorous theoretical point of view, the latter procedure is the preferred. Moreover, previous studies carried out by us indicated that explicit solvent molecules affect much more on the molecular structure than implicit solvent . Thus, it is the procedure that it is followed in the present work.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…From a rigorous theoretical point of view, the latter procedure is the preferred. Moreover, previous studies carried out by us indicated that explicit solvent molecules affect much more on the molecular structure than implicit solvent . Thus, it is the procedure that it is followed in the present work.…”
Section: Resultsmentioning
confidence: 98%
“…In our simulation, the number of water molecules considered is slightly lower, but the optimized clusters have the main water molecules H‐bonded to the microhelix. In the hydration of our microhelixes with 20 water molecules, several optimized clusters were obtained following the MSM methodology . In each microhelix, the most stable cluster was that with each Na atom surrounded by four water molecules (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By the same methodology, the relative energies of the different conformers have been determined in related nucleosides [34,46,47,48]. The global minimum calculated in these molecules by MP2/6-31G(d,p) was in accordance to that found by B3LYP/6-31G(d,p).…”
Section: Resultsmentioning
confidence: 55%
“…90°). The anti structures are the expected forms in the natural nucleosides that form the nucleotides and polynucleotides in biological systems [33,35,46,47,48]. The ratio anti/syn in conformers A is 0.8 in the low-energy group (<3 kcal/mol) but it increases up to 1.7 in the 3.0–8.5 kcal/mol range.…”
Section: Resultsmentioning
confidence: 99%